Quality Assurance in Mongolian Higher Education (International Journal of Environmental Sciences, 2025)
Quality assurance can be a driver for higher education institutions to achieve excellence in their activity. However, ensuring that the quality of higher education programs meets local and international standards simultaneously has become a great challenge in many countries. Globalization in higher education has resulted in a growing demand for quality education, in turn it causes challenges and obstacles to overcome. The aim of this paper is to present a general view on main aspects of quality assurance in Mongolian higher education. It provides an overview of curriculum accreditation of universities as well as university ranking process as a mechanism to ensure quality in higher education. From the study, although the quality assurance in Mongolian higher education is getting more consistent with the global standards, there are some weak areas that need to be addressed. From the study, it is concluded that the government involvement should be reduced in quality assessment process, and it should facilitate fair competition between universities.